(untitled) (Bangladesh Journal of Botany, 2020)
It was found that the pesticide droplets have always showed an elliptical shape when detecting the contact angle of the pesticide droplets on the Ken-Nian No. 1 corn leaves. In order to describe more accurately the spreading behavior of the pesticide droplets on these corn leaves, present authors have established a contact angle prediction model. In this experiment, the leaves in Ken-Nian No. 1 corn at jointing stage were used as test materials and were sprayed with different concentrations of Kresoxim-methyl water dispersant pesticide. The simulation test has used the modified HAD-HB contact angle tester to measure the four variates, longitudinal and horizontal spreading diameter named ‘a’ and ‘b’, longitudinal and lateral contact angle named ‘α’ and ‘β’. The mathematical relationship models between ‘α-ab’ and ‘β-ab’ were established by using Matlab. The Adjusted R-square of two models are above 0.98. The test results showed that the predicted values of the models were within ± 2 degrees of the actual measured value.